(untitled) - Huard, Pierre (Hanoi, 1990)
This book introduce the physical geography of Vietnam, a brief history of Vietnam. Vietnamese somatical structure, origin of Vienamese culture, characteristics of Vietnamese material culturu. Macro-microcosmic characteristics of Vietnamese spiritual culture...
Keywords: Việt Nam,Vietnam; Văn minh,Civilization